Clareamento caseiro versus dentifrícios clareadores para o tratamento da cor dentária: uma análise de custo-efetividade - Santos, Mariana Evangelista (2022)
This study aimed to analyze the cost-effectiveness of whitening toothpastes and at-home bleaching as treatments for tooth discoloration. A cost-effectiveness economic analysis was conducted and eight randomized clinical trials were selected based on the products used in this analysis: blue covarine dentifrices (BCD), hydrogen peroxide dentifrices (HPD), dentifrices without bleaching agents (CD, negative control), and 10% carbamide peroxide (CP10, positive control) at-home bleaching agents. The consumer/patient perspective was adopted, macro-costing techniques was used, and two decision tree models were performed considering the costs in the American and Brazilian markets. The color change evaluation (ΔE*ab) was used to calculate the effectiveness of tooth bleaching. The costs included in this analysis were direct, and the use of one tube of toothpaste per month during a year was assumed as the cost charged for CP10 bleaching. A probabilistic analysis was performed using a Monte Carlo simulation, and incremental cost-effectiveness ratios were obtained. CP10 at-home bleaching resulted in the highest cost-effectiveness compared to the use of dentifrices in both markets. In Brazil, HPD was more cost-effective than BCD and CD. In the US, the increased costs of HPD and BCD did not generate any whitening benefit compared to CD. CP10 at-home bleaching was more cost-effective than BCD and HPD for treating tooth discoloration in the Brazilian and American markets.